Statistical and anomalies analysis of the 50-year precipitation of the synoptic stations in Iran - mina mirian; mostafa karampoor; mohamd moradi; houshang ghemi; behrouz nasiri (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study is to determine the long-term variations in rainfall data as well as to identify wet and dry periods of 35 synoptic stations in Iran. In order to know the variation of rainfall in studied stations, average maps, coefficient of variation and skewness were drawn. Then, using the Mann-Kendall test, the significance of the trend on each station was tested at 95% confidence level. Finally, wet and dry periods were identified by using 20% high and low extreme rainfall during the 50-year study period. The results show that the general model of the country's regime is that the rainfall levels from the north to the south-east and from the west to the east of the country are reduced. The lowest values of the coefficient of variation and skewness are related to the northern regions especially the Caspian seaside and the highest amounts are in the southern regions, especially in the south and south-east. In general, the results of the Mann-Kendall test show that rainfall data in the seasonal scale, with the exception of several synoptic stations, do not show a significant trend. Most wet periods occur in the spring and the lowest in summer and the highest dry periods occur in the autumn and the lowest in spring. The number of droughts in the cold periods is significant. Also, the frequency of occurrence of dry periods is more than wet periods.